Birds and Bees, the 'R' Word and Zuma's p*nis: Censorship Avoidance Strategies in a South African Online Newspaper's Comments Section. - Mokwena, Lorato; Banda, Felix (Sexuality & Culture, 2019)
Although linguistic practices in online platforms continue to receive fair scholarly attention, limited research has been conducted on online censorship avoidance strategies in South Africa about online newspapers. We use notions of semiotic remediation on comments on two articles on a nude painting of former South African President Jacob Zuma in a popular South African online publication, SowetanLive, to show how the commentators creatively avoid censorship and to operationalise their right of freedom of expression. Particularly, we show the various ways commentators transform and recontexatualise existing semiotic affordances of punctuation marks, letters, digits, South African English, indigenous South African languages and cultural knowledge to achieve new and extended meanings while simultaneously avoiding censorship. This paper demonstrates that censorship strategies are mostly employed to comments related to: (1) racism; (2) gender identities and (3) sex. As extensive as these censorship strategies are, the potential inflammatory content is intentionally made to be decipherable by participants which problematises the concept of 'censorship'. This paper argues that South Africa is to a large extent still a conservative country that grabbles with socio-political issues such as racism, gender identities, objectification of black bodies and so forth. However the readership of SowetanLive is finding ways to question such conservatism through online platforms and censorship avoidance strategies.